2021
DOI: 10.1161/hypertensionaha.120.16472
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Blood Pressure Control and Coronavirus Disease 2019 Outcomes in 45 418 Symptomatic Patients With Hypertension

Abstract: Hypertension has been identified as a risk factor for COVID-19 and associated adverse outcomes. This study examined the association between pre-infection blood pressure (BP) control and COVID-19 outcomes using data from 460 general practices in England. Eligible patients were adults with hypertension who were tested or diagnosed with COVID-19. BP control was defined by the most recent reading within 24months of the index date (01/01/2020). BP was defined as controlled (<130/80mmHg), raised (130/80-139/89mmH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 24 publications
3
41
1
1
Order By: Relevance
“…Current findings from Sheppard et al [ 12 ] show that patients with BP < 130/80 mm Hg had higher odds of COVID-19 death than patients with BP 140/90–159/99 mm Hg. BP values 130/80–139/89 mmHg and BP ≥ 160/100 mmHg were not associated with COVID-19-related death.…”
Section: Discussionmentioning
confidence: 98%
“…Current findings from Sheppard et al [ 12 ] show that patients with BP < 130/80 mm Hg had higher odds of COVID-19 death than patients with BP 140/90–159/99 mm Hg. BP values 130/80–139/89 mmHg and BP ≥ 160/100 mmHg were not associated with COVID-19-related death.…”
Section: Discussionmentioning
confidence: 98%
“…The role of hypertension in acute COVID-19 is not clear - initially reported as a possible risk factor for severe COVID-19 (in excess in severe versus nonsevere cases)(37), has not been shown to be a robust predictor of severity with age-hypertension interactions even decreasing risk(35) and improved blood pressure control correlating to worse outcomes (38). Antihypertensive medications may impact disease course, with preliminary results indicating effects that may vary by race(39).…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies at the onset of the pandemic reported high prevalence of hypertension and other comorbidities and mortality from COVID-19 (77,78). In a case-series study of 5,700 patients with COVID-19 in New York, hypertension (56.6%), obesity (41.7%), and diabetes (33.8%) were the most frequent comorbidities (77).…”
Section: Hypertensionmentioning
confidence: 99%
“…show that patients with COVID-19 and hypertension have a higher mortality risk when compared with non-hypertensives (77)(78)(79).…”
Section: Hypertensionmentioning
confidence: 99%